Transformasi Layanan Perpustakaan Berbasis Inklusi Sosial dalam Pemberitaan Media Massa Cetak Indonesia - Santoso, Endy; Mayesti, Nina (Kementerian Sekretariat Negara Republik Indonesia, 2022)
This research discusses transformation of social inclusion-based library services in Indonesia printed mass media through the use of vocabulary and grammar. This research is a qualitative descriptive study using the discourse analysis method of Roger Fowler, et al. The results of this study reveal that there are reality construction processes built through the use of vocabulary and grammar, namely in the use of vocabulary there has been a classification process, a discourse battle process, and vocabulary as a form of marginalization. In addition, through the use of grammar, the perpetrator is removed as an effect of using the passive form and nominalization. This research suggests that the National Library of Indonesia needs to pay attention to the use of vocabulary and grammar as a means of enhancing the role of the National Library in society. In addition, it is necessary to increase the role of librarians in various activities and programs carried out by libraries, including the transformation programs of social inclusion-based library services. Keywords: transformation, news, mass media, discourse analysis model of roger fowler, et al.